(untitled) (Gestión y Gerencia, 2021)
Social organizations constitute the fundamental pillar to produce knowledge as an educational-scientific epistemic horizon directed to a new reality of onto-epistemological frameworks from various fields in social and administrative sciences, involving institutions and communities, specifically public libraries, focused on overcoming their weaknesses by developing mission, vision, social responsibility to offer quality and dissemination of knowledge, designed to raise its internal and social relevance and insert itself as a socially responsible and self-sustaining organization.- The research purpose is to reflect on knowledge management as a generator of social responsibility integrated into the Agora Model for organizational learning in sustainable public libraries. The theoretical scaffolding was based on the authors Hessen (1926), Guedez (2000), IFLA/UNESCO (2001), Drucker (2006), Parra (2013) and Ahumada and Busto (2004) of the Ágora Model. The methodology is based on the guidelines of Balestrini (2006). Analytical reflections indicate that libraries need to evolve as a learning, intelligent organization, guided by the social construction of integrated knowledge in learning communities, with organizational identity, quality training on sustainable development of economic, ecological, productive and social balance.